Maternal and Fetal Alternative Complement Pathway Activation in Early Severe Preeclampsia - Hoffman, M. Camille (2013)
PROBLEM: We sought to determine whether alternative complement activation fragment Bb (Bb) levels are elevated in the maternal, fetal, and placental blood in cases of severe preeclampsia (PE) compared with normotensive controls. METHOD OF STUDY: This was a cross-sectional study of women admitted at ≥24 weeks gestation with or without severe PE. Maternal plasma was collected at the time of enrollment. Umbilical venous cord and intervillous space blood were collected at delivery. Plasma Bb levels were assessed using ELISA. Bb levels were compared between cases and controls. RESULTS: Median Bb levels were higher in the maternal plasma of severe PE subjects (n = 24) than in controls (n = 20), 1.45 ± 1.03 versus 0.65 ± 0.23 μg/mL, P < 0.001. In umbilical venous plasma, Bb levels were higher in severe PE subjects (n = 15) compared with controls (n = 15), 2.48 ± 1.40 versus 1.01 ± 0.57 μg/mL, P = 0.01. CONCLUSION: Activation fragment Bb is increased in the maternal and umbilical venous blood of cases of severe PE when compared with normotensive controls. These data provide support for alternative complement pathway involvement in the pathogenesis of severe PE and demonstrate that alternative complement activation occurs not only in the maternal but also in the fetal compartment.